Adaptation and Validation of the Psychological Need Thwarting Scale in Spanish Physical Education Teachers - Cuevas, R.; Sánchez-Oliva, D.; Bartholomew, K.; Ntoumanis, Nikos; García-Calvo, T. (Cambridge University Press, 2015)
Drawing from self-determination theory (SDT; Deci & Ryan, 1985; Ryan & Deci, 2002), the aim of the study was to adapt and validate a Spanish version of the Psychological Need Thwarting Scale (PNTS; Bartholomew, Ntoumanis, Ryan, & Thørgersen-Ntoumani, 2011) in the educational domain. Psychological need thwarting and burnout were assessed in 619 physical education teachers from several high schools in Spain. Overall, the adapted measure demonstrated good content, factorial (χ2/gl = 4.87, p < .01, CFI = .95, IFI = .96, TLI = .94, RMSEA = .08, SRMR = .05), and external validity, as well as internal consistency (α ≥ .81) and invariance across gender. Moreover, burnout was strongly predicted by teachers’ perceptions of competence (β = .53, p ≤ .01), autonomy (β = .34, p ≤ .01), and relatedness (β = .31, p ≤ .01) need thwarting. In conclusion, these results support the Spanish version of the PNTS as a valid and reliable instrument for assessing the understudied concept of psychological need thwarting in teachers.